2017
DOI: 10.5897/ajfs2016.1522
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological performance of Hazard Analysis Critical Control Point (HACCP)-based food safety management systems: A case of Nile perch processing company

Abstract: This study aimed at giving insight into microbiological safety output of a Hazard Analysis Critical Control Point (HACCP)-based Food Safety Management System (FSMS) of a Nile perch exporting company by using a combined assessment, FSMS-diagnosis and actual microbiological assessment. The FSMS diagnosis indicated FSMS activities at an average level operating in moderate-risk context level but with good system output. Likewise, microbiological assessment revealed a better system output with respect to pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…slaughtering house, retail shop, and processing plant, along the lamb chain. Kussaga et al ( 42 ) also reported the overall context score was 2 (moderate-risk) in a Nile perch processing company in Tanzania.…”
Section: Discussionmentioning
confidence: 96%
“…slaughtering house, retail shop, and processing plant, along the lamb chain. Kussaga et al ( 42 ) also reported the overall context score was 2 (moderate-risk) in a Nile perch processing company in Tanzania.…”
Section: Discussionmentioning
confidence: 96%
“…Five microbiological parameters including indicators of general process hygiene (Total Viable Counts, TVC), fecal hygiene (total coliforms and Escherichia coli), personnel hygiene (Staphylococcus aureus), and food safety (Listeria monocytogenes) were selected and analyzed (Jacxsens et al, 2009;Kussaga et al, 2017). Testing for TVC aimed at assessing the quality of raw materials, effectiveness of the handling procedures and hygiene conditions during processing, sanitary conditions of equipment and utensils, and time/temperature profile during storage and distribution.…”
Section: Selection Of Microbiological Parametersmentioning
confidence: 99%
“…The counts beyond the acceptable limits for TVC (5.14 -8.68 Log CFU/25 g) and S. aureus (3.08-5.49 Log CFU/25 g) of the analysed samples from the majority of processors in Cluster I are due to the observed unhygienic handling conditions of raw materials and finished products, poor sanitation and personal hygiene, use of non-food grade equipment (wooden materials as drying racks which are difficult to clean and sanitize hence harbouring microorganisms) and inadequate packaging conditions. According to Norman (1999) and Kussaga et al (2017), possible causes of food contamination by enteric microorganisms (such as, Enterobacteriaceae and E. coli) are inadequate procedures of handling, packaging, storage, sanitation, and personal hygiene.…”
Section: Assessment Of Microbiological Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Food safety management system is a company with certain practice to conduct and ensure activities the safety of food. Conducting acts with the objective to maintain products alongside with their processes in adequate borders in realizing food safety where the acts are concerning the examination of performing and organizing ways will crucially diverse [7], [8].…”
Section: Introductionmentioning
confidence: 99%